Low‐temperature radiant cooling panel for hot and humid climate - Huang, Gongsheng; Zhang, Nan; Liang, Yuying (CLIMA 2022 conference, 2022)
In this paper, the heat transfer and thermal environment of air‐layer integrated radiant cooling panel (AiCRCP) was studied experimentally. AiCRCP was proposed in 1963, which was characterized by the use of an infrared‐radiation transparent (IRT) membrane to separate the panel’s radiant cooling surface from its external air‐contact surface. Therefore, the panel’s radiant cooling surface temperature can be reduced to increase the cooling capacity, while its external air‐contact surface, due to the thermal resistance provided by the air layer and the IRT membrane, can be easily maintained at a high temperature to reduce condensation risks. The thermal performance of AiCRCP was investigated using a prototype. Several scenarios were tested to analyze the thermal performance of prototype, and the cooling capacity of the AiCRCP was also investigated according to the thermal performance of the prototype. The results demonstrated that this new type of radiant cooling systems could be more preferable to be implemented in hot and humid climates.